Emphysematous gastritis developing after isolated cardioembolic event - Muna Aguon, Paul; Aasen, Tyler; Shinar, Brenda (International Journal of Medicine, 2018)
Emphysematous gastritis is a very rare disease associated with a high mortality rate, making prompt recognition and early treatment of the underlying cause essential. We present a case of emphysematous gastritis developing after a cardio embolic-related acute ischemic injury to the gastric mucosa.